(untitled) (Communication & Society, 2012)
Postmodernism, a culture of vague boundaries, boosted values such as individualism and superficial character, with the Mass Media as a crucial factor in spreading them. The Internet is an heir of this period, but took on a life of its own, becoming the favourite information source for the population, and also an economic icon. The Internet put an end to the fragmentation of the media and introduced a bidirectional nature to communications. It is a multipurpose tool that generates values and changes (in reading, attention, memory or culture), requiring a critical evaluation of the new Me Generation axiology.